Chronic fluoxetine treatment increases daytime melatonin synthesis in the rodent - Gillian W Reierson (Dove Medical Press, 2009)
Gillian W Reierson, Claudio A Mastronardi, Julio Licinio, Ma-Li WongCenter on Pharmacogenomics, Department of Psychiatry and Behavioral Sciences, University of Miami Miller School of Medicine, Miami, FL, USAAbstract: Circadian rhythm disturbances can occur as part of the clinical symptoms of major depressive disorder and have been found to resolve with antidepressant therapy. The pineal gland is relevant to circadian rhythms as it secretes the hormone melatonin following activation of the cyclic adenosine monophosphate (cAMP) signaling cascade and of arylalkylamine N-acetyltransferase (AA-NAT), the rate-limiting enzyme for its synthesis. Cyclic AMP is synthesized by adenylate cyclases (AC) and degraded by phosphodiesterases (PDEs). Little is known about the contribution of the PDE system to antidepressant-induced alterations in pineal cAMP signaling and melatonin synthesis. In the present study we used enzyme immunoassay to measure plasma melatonin levels and pineal cAMP levels and as well as quantitative real-time polymerase chain reaction to measure pineal expression of PDE, AC, and AA-NAT genes in rats chronically treated with the prototypic antidepressant fluoxetine. We found elevated melatonin synthesis with increased pineal AA-NAT gene expression and daytime plasma melatonin levels and downregulated cAMP signaling with increased PDE and unchanged AC pineal gene expression, and decreased content of pineal cAMP. We conclude that chronic fluoxetine treatment increases daytime plasma melatonin and pineal AA-NAT gene expression despite downregulated pineal cAMP signaling in the rodent.Keywords: antidepressant, melatonin, pineal, nucleotides, cyclic, phosphodiesterase, rat